The chemistry of precipitation, throughfall and stemflow in two holm oak (Quercus ilex L.) forests under a contrasted pollution environment in NE Spain. - Rodrigo, a; Avila, A.; Roda, F. (The Science of the total environment, 2003)
Atmospheric deposition was studied through measurements of bulk deposition, throughfall and stemflow at two sites of contrasted exposure to pollution in the Montseny mountains (Northeastern Spain). To explore the contribution of local or distant sources at both sites, concentration data and precipitation amounts (log transformed) for both bulk deposition and net throughfall were fitted by linear regression. These models indicated the more important contribution of washout scavenging processes and dry deposition at the pollution exposed site. This is relevant in the context of Mediterranean holm oak forests: up to now, most of the studies have been conducted in protected remote sites and were little representative of the fluxes in forests close to industrial activity, traffic, agriculture and residential areas.
The following values have no corresponding Zotero field: accession-num: 12670768
Keywords: bulk deposition; Dry deposition; Holm oak forest; Leaching; N uptake; throughfall

metal contents in Parmelia caperata(L.) Ach. compared to bulk deposition, throughfall and leaf-wash fluxes in two holm oak forests in Montseny (NE Spain) - Rodrigo, A.; Avila, A.; Gómez-Bolea, A. (Atmospheric Environment, 1999)
The metal concentrations of V, Cr, Co, Ni, Cu, Zn, Cd, Hg and Pb were analysed in distilled water extracts of Parmelia caperata and in bulk deposition, throughfall and an experimental in situ washing of leaves at two forests at Montseny (NE Spain) submitted to di¤erential exposure to the industrial and tra¦c activities around Barcelona. Lichen concentra- tions of Zn, Cu, V, and Cd were higher at the site of greater exposure to pollutants. Consistently, there was higher dry deposition of these metals at the more exposed site. The order of abundance of trace metals in the lichen was similar to that in the deposition variables, although Pb and Cu had intermediate concentrations in the lichen but were very low in the deposition measurements. This indicated the higher a¦nity of Pb and Cu for the exchange sites in the lichen cell wall and the fact that lichens accumulated Pb for the last 12Ð18 y when emissions were much higher than today. The ability of Parmelia caperata to indicate the deposition of heavy metals, together with its easy sampling and handling, its broad distribution and its easy identiÞcation suggest that the lichen extract procedure described here could be used to establish gradients of atmospheric deposition of heavy metals at a general geographic level
Keywords: atmospheric deposition; bulk deposition; parmelia caperata; Quercus ilex; throughfall; trace metal

Mineralogical composition of African dust delivered by red rains over northeastern Spain - Avila, A.; QueraltMitjans, I.; Alarcon, M. (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 1997)
The African dust deposition, mineralogy, source regions, and influence on rain chemistry were analyzed for a site in the Montseny mountains (Catalonia, northeastern Spain) for the period August 1, 1983, through August 1, 1994. Dust deposition was highly variable: two events (collected on November 9-11, 1984, and March 22-25, 1991) accounted for 62% of the total dust input in the 38 red rain events recorded in the period. The average annual dust deposition was 5.3 g m(-2) (SE 2.6). Three source regions in the African continent were identified with back trajectory analysis: (1) Western Sahara, (2) Moroccan Atlas, and (3) Central Algeria. Events from the Moroccan Atlas predominated in terms of number of events, amount of rainfall, and dust deposition. The meteorological situations during red rains were identified: Western Sahara events occurred principally with a depression at high latitudes (50 degrees N) forming a trough in the North Atlantic, Moroccan Atlas events occurred with a depression in front of Portugal, and events from central Algeria were associated with a depression over Spain or North Africa. By order of abundance (median of n=13) the minerals identified in the dust by X ray diffraction were as follows: illite > quartz > smectite > palygorskite > kaolinite > calcite > dolomite > feldspars. Differences in mineralogy between source regions were significant for smectite, kaolinite, quartz, and dolomite. Smectite and kaolinite content was highest in the Algerian events, while quartz and dolomite content was lowest. Events from the Moroccan Atlas had the lowest smectite and kaolinite. The red rain soluble chemistry was clearly influenced by the dissolution of calcite (high alkalinity, calcium concentration and basic pH) and by marine components (high Na+, Cl- and Mg+2 concentrations). Because of the very alkaline character of red rains they had a strong weight on the annual mean pH of rainwater. This was reflected by the significant relationship (r=0.71, p<0.01) between the percentage of annual precipitation as red rain and annual mean precipitation pH. Red rains provided 25-45% of the annual dissolved input of the major ions in precipitation and 34% of the calcium required for helm oak (Quercus ilex L.) forest growth at the study site.
APSAPSThe following values have no corresponding Zotero field: pub-location: 2000 FLORIDA AVE NW, WASHINGTON, DC 20009 USA publisher: AMER GEOPHYSICAL UNION
Keywords: Africa; dust deposition; Montseny mountains; Quercus ilex L.